Espesor del esmalte en dientes permanentes de perro - Hernández, S.Z. (2021)
Enamel, the hardest substance in the body, covers the crown of the teeth of mammals, reptiles and amphibians. The objective of this work was to evaluate the thickness of the enamel of permanent dog teeth and determine its variations according to the site of the crown, the type of tooth and the size of the animal. A total of 317 teeth (incisors, canines, premolars and molars) extracted from 8 dogs were studied. The teeth were longitudinally sectioned in the vestibule-palatine / lingual direction with a diamond disc at different levels and observed with a binocular loupe with 20X magnification. Enamel thickness measurements were taken with the aid of an eyepiece with a micrometer scale. The mean value of tooth enamel thickness (n = 1618) was 0.324 ± 0.11 mm, with a range between 0.05 mm and 1.00 mm. The observations made in relation to the thickness of the enamel of dog teeth allow concluding i) that it would be much lower than that reported in humans; ii) that it varies according to the sector of the crown (being greater in cusps and lower in the center of the occlusal surfaces); iii) that the smaller the crown size, the greater the relative thickness and iv) that the smaller the skull, the greater the relative thickness.